Effect of Aging-Induced Dioxolane Polymerization on the Electrochemistry of Carbon-Coated Lithium Sulfide - Lodovico, Lucas; Varzi, Alberto; Passerini, Stefano (Frontiers in Chemistry, 2020)
Lithium sulfide-based materials have been considered as potential positive electrodes for the next generation batteries. Lithium sulfide is the fully lithiated form of sulfur, i.e., they share the same high theoretical capacity. However, it has the benefit of already containing lithium, which allows making cells with lithium-free negative electrodes. Lithium sulfide, however, shares with sulfur the polysulfide dissolution drawback upon cycling. One possible solution to this problem is to envelop the active material particles with carbonaceous materials. In this work, we investigate the effect of a nitrogen-rich carbon coating on lithium sulfide particles. The effect of such coating on the surface properties and electrochemistry of lithium sulfide cathodes is investigated in details, in particular, regarding its interaction with fresh vs. aged electrolyte. The polymerization of dioxalane (DOL) due to ageing is found to affect the electrochemistry of lithium sulfide and, interestingly, to improve the cycling performance.